2001
DOI: 10.1128/iai.69.9.5235-5242.2001
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Mitogen-Activated Protein Kinase Pathways inStaphylococcus aureusInvasion of Normal Osteoblasts

Abstract: Staphylococcus aureus invades osteoblasts and can persist in the intracellular environment. The present study examined the role of osteoblast mitogen-activated protein kinase (MAPK) pathways in bacterial invasion. S. aureus infection of normal human and mouse osteoblasts resulted in an increase in the phosphorylation of the extracellular signal-regulated protein kinases (ERK 1 and 2). This stimulation of ERK 1 and 2 correlated with the time course of S. aureus invasion, and bacterial adherence induced the MAPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 58 publications
3
37
0
Order By: Relevance
“…The fact that only the development of those paranasal sinuses which have post-natal growth (frontal and sphenoidal) is compromised might indicate that this effect is secondary to chronic post-natal upper airways infection and inflammation [16,17], and hypothetically related to the premature ossification of the cartilage surrounding the paranasal recesses [16, 17.] The higher than normal prevalence in SCD would support this hypothesis. In animal models it has been demonstrated that airfilled spaces in the cranium are formed by invasion of nasal mucous epithelium into neighbouring nasal capsule cartilages [18].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that only the development of those paranasal sinuses which have post-natal growth (frontal and sphenoidal) is compromised might indicate that this effect is secondary to chronic post-natal upper airways infection and inflammation [16,17], and hypothetically related to the premature ossification of the cartilage surrounding the paranasal recesses [16, 17.] The higher than normal prevalence in SCD would support this hypothesis. In animal models it has been demonstrated that airfilled spaces in the cranium are formed by invasion of nasal mucous epithelium into neighbouring nasal capsule cartilages [18].…”
Section: Discussionmentioning
confidence: 99%
“…30) Mitogen-activated protein kinase (MAPK) family members are involved in host cell invasion by several pathogenic bacteria. [17][18][19][20][21] Invasion of epithelial cells represents a potential pathogenic mechanism for K. pneumoniae. We explored the role of mitogen-activated protein kinase kinases (MEK 1/2) and the extracellular signalregulated kinases (ERK 1/2) in K. pneumoniae invasion.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Pretreatment with the MEK1/2 inhibitor PD98059 significantly reduced K. pneumoniae 03183 uptake by T 24 cells (Fig. 1).…”
Section: Effects Of Rhmgn2 On Invasion Activity Of K Pneumoniae 0318mentioning
confidence: 99%
“…Staphylococcus aureus strain UAMS-1 (ATCC 49230) is a human osteomyelitis clinical isolate (15). Staphylococcus carnosus (ATCC 51365) is a nonpathogenic species with a reduced ability to invade osteoblasts (11). Strains N1, N2, N3, N4, and N5 are Staphylococcus aureus nasopharyngeal isolates kindly provided by Vance G. Fowler, Jr. (Duke University Medical Center).…”
Section: Methodsmentioning
confidence: 99%
“…Although both constitutive COX (COX-1) and inducible COX (COX-2) are expressed in mouse osteoblasts, the expression of COX-2 is markedly induced by several proinflammatory cytokines, such as interleukin 6 (IL-6). Bost et al (5,11) have reported that S. aureus-infected osteoblasts produce high levels of IL-6, which have been shown to modulate the activity of bone-resorptive osteoclasts either directly or indirectly (21,45). It has also been determined that PGE 2 can upregulate RANK-L expression in osteoblasts (16,17,54,57).…”
mentioning
confidence: 99%